Analisis Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Pelanggan Serta Dampaknya Terhadap Peningkatan Penjualan Iphone di Toko Yusuf by Phone - Azuwandri, Azuwandri; Gustini, Gustini; Eka Putra, M Bima; Fhikri, Rijalul (Jurnal Adminitrasi Bisnis Nusantara, 2025)
This study aims to analyze the influence of product quality and price on customer satisfaction and its impact on the increase in iPhone sales at Yusufbyphone Store. The background of this research is based on the importance of maintaining product quality and setting competitive prices to enhance customer satisfaction in the highly competitive smartphone market. This research employs a quantitative approach using a survey method, where data were collected through questionnaires distributed to 100 respondents who had purchased products at Yusufbyphone Store. The data analysis technique used is multiple linear regression to examine the relationships between variables. The results of the study show that product quality has a positive and significant influence on customer satisfaction. Price also has a positive impact on customer satisfaction, although its effect is not as strong as that of product quality. Furthermore, customer satisfaction significantly influences the increase in iPhone sales at Yusufbyphone Store. These findings indicate that efforts to improve product quality and offer prices that meet customer expectations can enhance satisfaction, ultimately leading to increased sales.